The Impact of CSR on Employee Performance: With The Mediation of Employee Trust and Employee Behavior (A Case Study of Companies in Bekasi and Jakarta) - Setyaningrum, Retno Purwani; Haryono, Tulus (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2018)
The Researches on Corporate Social Responsibility (CSR) tends to focus on stakeholders and external outcomes. The impact of CSR on employee performance is still rarely discussed in many studies. This study aims to determine how the impact of CSR affects employee performance and the role of employee trust and employee behavior as a mediator at 3 companies in Bekasi and Jakarta. Every company has a responsibility to develop its environment through social programs. The research questions in this study are: (1) The impact of CSR on Employee performance, (2) The impact of CSR on employee trust (3) The impact of employee trust on employee performance (4) The impact of CSR on employee behavior (5) The impact of employee behavior on employee performance.Â The sample used in this study was 246 employees from companies in Bekasi and Jakarta District. Data collection method used in this study was questionnaire and forum group discussions (FGD), while analytical method used was SEM Warps PLS.The findings of this study indicate that CSR does not impact directly the employee performance. The CSR indicator that needs to be considered is ethical, where the companies are suggested to have a CSR department. Where employees have lack knowledge about environmental work, environmental laws regarding material sources, emissions, and so on. So that employees realize and understand the importance of having attention and responsibility to the environment. CSR has a significant impact on employee trust, employee trust has a significant impact on employee performance, CSR has a significant impact on employee behavior, and employee behavior significantly impact employee performance. Employee trust and employee behavior mediate the impact of CSR on Employee performance.Keywords: CSR, employees trust, employee behavior, employee performance